1987
DOI: 10.1002/cber.19871200627
|View full text |Cite
|
Sign up to set email alerts
|

Synthese, Photolyse und Thermolyse eines 1,4,4‐Trialkyl‐4,5‐dihydro‐5‐methylen‐1H‐1,2,3‐triazols. Hoch diastereoselektive Bildung des (E)‐2,2‐Dimethyl‐N‐neopentyl‐1‐cyclopropanimins

Abstract: Das 3,5-Dihydro-4H-l,2,3-triazol-4-on 13 reagiert glatt rnit Organolithiumverbindungen zu den tertiiren Alkoholen 14. Peterson-Olcfinierung oder -vicl bcsscr -Wittig-Olcfinicrung von 13 ergeben das erstc Dihydromethylen-l,2,3-triazol 17. Bcim Bestrahlcn ( h 2 320 nm) eliminiert 17 Stickstoff und bildet quantitativ und diastereoselektiv ( > 98% d.e.) das Cyclopropanimin (E)-22. Bei 70 C isomerisiert diescs rnit den Geschwindigkeitskonstanten k t L = 9.0. l O -' s -' und kll. = 15.0. . s-I).Obviously, the geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…In addition to the expected pyrroline products 4,e thylene gas ( 1 HNMR signal at d = 5.41 ppm) was formed as well as isonitrile 5 (42 %; confirmed by X-ray crystallographic [a] 36:64 21:79 29:71 E/Z (PSS at 455 nm) [b] 99:1 99: structure determination), most likely by ap hotoinduced [2+ +2] cycloreversion reaction. [16,17] Most importantly,the two diastereomeric spirocyclic pyrroline products endo-4/exo-4 were obtained with an unbalanced d.r. value of 58:42, also indicating apreferred directionality in the C = Nbond rotation (see below).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the expected pyrroline products 4,e thylene gas ( 1 HNMR signal at d = 5.41 ppm) was formed as well as isonitrile 5 (42 %; confirmed by X-ray crystallographic [a] 36:64 21:79 29:71 E/Z (PSS at 455 nm) [b] 99:1 99: structure determination), most likely by ap hotoinduced [2+ +2] cycloreversion reaction. [16,17] Most importantly,the two diastereomeric spirocyclic pyrroline products endo-4/exo-4 were obtained with an unbalanced d.r. value of 58:42, also indicating apreferred directionality in the C = Nbond rotation (see below).…”
Section: Methodsmentioning
confidence: 99%
“…[16,17] Most importantly,the two diastereomeric spirocyclic pyrroline products endo-4/exo-4 were obtained with an unbalanced d.r. [16,17] Most importantly,the two diastereomeric spirocyclic pyrroline products endo-4/exo-4 were obtained with an unbalanced d.r.…”
Section: Methodsmentioning
confidence: 99%
“…structure determination), most likely by ap hotoinduced [2+ +2] cycloreversion reaction. [16,17] Most importantly,the two diastereomeric spirocyclic pyrroline products endo-4/exo-4 were obtained with an unbalanced d.r. value of 58:42, also indicating apreferred directionality in the C = Nbond rotation (see below).…”
Section: Methodsmentioning
confidence: 99%
“…These strained aziridines are converted into 2-amidoallyl cations 2 (Scheme ) upon acidic treatment that, in turn, may then be intercepted by suitably disposed dienes, exemplified by the formation of tetracycle 3 from MA 1 . Building from this work, we explored the possibility that azatrimethylene methane (ATMM) diyls might behave analogously . Feldman has shown that the thermal dipolar cycloaddition of azidoethyl allenes leads to loss of dinitrogen and formation of ATMM intermediates that, in the conjugated systems under study, immediately undergo ring closure, leading to cyclopenta­[ b ]­pyrrole derivatives ( 4 → 5 → 6 , Scheme ).…”
mentioning
confidence: 99%